Education and training for medicines development, regulation, and clinical research in emerging countries - Kerpel-Fronius, Sandor; Rosenkranz, Bernd; Allen, Elizabeth; Bass, Rolf; Mainard, Jacques D.; Dodoo, Alex; Dubois, Dominique J.; Hela, Mandisa; Kern, Steven; Massud, Joao; Silva, Honorio; Whitty, Jeremy (Frontiers in Pharmacology, 2015)
The aim of this satellite workshop held at the 17th World Congress of Basic and Clinical Pharmacology (WCP2014) was to discuss the needs, optimal methods and practical approaches for extending education teaching of medicines development, regulation and clinical research to Low and Middle Income Countries (LMIC’s). It was generally agreed that, for efficiently treating the rapidly growing number of patients suffering from non-communicable diseases, modern drug therapy has to become available more widely and with a shorter time lag in these countries. To achieve this goal many additional experts working in medicines development, regulation and clinical research have to be trained in parallel. The competence-oriented educational programs designed within the framework of the European Innovative Medicine Initiative-PharmaTrain (IMI-PhT) project were developed with the purpose to cover these interconnected fields. In addition, the programs can be easily adapted to the various local needs, primarily due to their modular architecture and well defined learning outcomes. Furthermore, the program is accompanied by stringent quality assurance standards which are essential for providing internationally accepted certificates. Effective cooperation between international and local experts and organizations, the involvement of the industry, health care centers and governments is essential for successful education. The initiative should also support the development of professional networks able to manage complex health care strategies. In addition it should help establish cooperation between neighboring countries for jointly managing clinical trials, as well as complex regulatory and ethical issues.